Becoming - Obama, Michelle, 1964- (New York : Crown, an imprint of the Crown Publishing Group, 2018)
"An intimate, powerful, and inspiring memoir by the former First Lady of the United States. When she was a little girl, Michelle Robinson's world was the South Side of Chicago, where she and her brother, Craig, shared a bedroom in their family's upstairs apartment and played catch in the park, and where her parents, Fraser and Marian Robinson, raised her to be outspoken and unafraid. But life soon took her much further afield, from the halls of Princeton, where she learned for the first time what if felt like to be the only black woman in a room, to the glassy office tower where she worked as a high-powered corporate lawyer--and where, one summer morning, a law student named Barack Obama appeared in her office and upended all her carefully made plans. Here, for the first time, Michelle Obama describes the early years of her marriage as she struggles to balance her work and family with her husband's fast-moving political career. She takes us inside their private debate over whether he should make a run for the presidency and her subsequent role as a popular but oft-criticized figure during his campaign. Narrating with grace, good humor, and uncommon candor, she provides a vivid, behind-the-scenes account of her family's history-making launch into the global limelight as well as their life inside the White House over eight momentous years--as she comes to know her country and her country comes to know her. [This book] takes us through modest Iowa kitchens and ballrooms at Buckingham Palace, through moments of heart-stopping grief and profound resilience, bringing us deep into the soul of a singular, groundbreaking figure in history as she strives to live authentically, marshaling her personal strength and voice in service of a set of higher ideals. In telling her story with honesty and boldness, she issues a challenge to the rest of us: Who are we and who do we want to become?"--Jacket
Becoming me -- Becoming us -- Becoming more -- Epilogue
AAPGMAIN copy has bookplate: Smithsonian Institution Libraries, Gift of Ellen G. Miles
NMAF copy 39088019685700 and 39088019685742 Purchased with Adopt-a-Book Funds.
Keywords: Obama, Michelle, -- 1964-; Presidents' spouses -- United States -- Biography; African American women lawyers -- Illinois -- Chicago -- Biography; Legislators' spouses -- United States -- Biography; Nonfiction; Autobiographies; Biographies; Autobiographies; Biographies; Biography